RE-ENFORCING RADICALISATION WITH BAD PR? THE NIGERIAN ARMY'S HANDLING OF BOKO HARAM - Yan St-Pierre (Journal for Deradicalization, 2015)
The organisation formerly known as Jamā'at Ahl as-Sunnah lid-Da'wah wa'l-Jihād' and currently known as Wilāyat Gharb Ifrīqīyyah, better known as Boko Haram, rose to international prominence in April 2014, when it kidnapped over 250 school girls from the Nigerian village of Chibok. Although the organisation is active since 2002 and began its violent insurgency in 2009, the mass kidnapping of the “Chibok Girls” attracted worldwide attention to the conflict, in large part due to the #BringBackOurGirls campaign, which was actively supported by U.S. First Lady Michelle Obama.